A 3D DC Electric Field Meter Based on Sensor Chips Packaged Using a Highly Sensitive Scheme - Pengfei Yang; Xiaolong Wen; Xiaonan Li; Zhaozhi Chu; Chunrong Peng; Shuang Wu (Micromachines)
This study presents a 3D DC electric field meter (EFM) that uses three identical 1D MEMS chips. The shielding electrodes and sensing electrodes of the MEMS chips employ a combination of rigid frames and short strip-type beams to improve vibrational stability. To enhance sensitivity, our MEMS chips feature inner convex packaging covers. Moreover, the integrated design and wireless transmission efficiently eradicate the impact of ground potential on detection results. Detailed simulations have been conducted to analyze the electric field distribution within the chip package and the electric field distribution on the EFM’s surface. A prototype was then developed, calibrated, and validated. The test results indicate that the sensitivity of our proposed 3D EFM is at least 4.64 times higher than the highest sensitivity observed in previously reported MEMS 3D EFMs. The maximum relative deviation is a mere 2.2% for any rotation attitude. Remarkably, even in high humidity conditions, the EFM’s linearity remains within 1%. Additionally, the resolution of any single axis is less than 10 V/m.